Progressivity comparisons - Valentino Dardoni; Peter J. Lambert (Institute for Fiscal Studies (IFS), 2000)
Analysts should correct for distributional differences before undertaking local progressivity comparisons between income tax or tax and benefit schedules. A transplant-and-compare procedure is advocated, involving 'importation' of the schedule from one regime into another, or from both into a reference scenario. The residual progression ordering over transplanted schedules then assures a global ordering of original regimes by Lorenz or Suits curves. The algorithm is advocated for use only when transplantation functions are isoelastic, and is illustrated for the Canadian, Israeli and UK tax and benefit systems.
Keywords: 330; Steuerprogression; Vergleich; Theorie